2016
DOI: 10.4314/njp.v43i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative colitis in a Nigerian child: case report

Abstract: Ulcerative colitis (UC) is a chronic re-occuring inflammatory disease affecting mainly the colon. It is more prevalent in the United Kingdom, North America Scandinavia and less common in southern Europe, Asia and Africa. Commonly, UC is suspected in patients presenting with bloody diarrhoea, tenesmus, abdominal pain, and, when severe, weight loss, fatigue, and vomiting. Perhaps one child so far with UC has been reported southwest geo-political zone of Nigeria. We here report the first case of ulcerative coliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the pediatric age group, there are even fewer reports of IBD in Nigeria. Senbanjo et al [11] and Ekanem et al [12] reported five cases of IBD in Nigerian children and UC in a male adolescent, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the pediatric age group, there are even fewer reports of IBD in Nigeria. Senbanjo et al [11] and Ekanem et al [12] reported five cases of IBD in Nigerian children and UC in a male adolescent, respectively.…”
Section: Introductionmentioning
confidence: 99%